Varietal Assessment, Heritability Estimates and Correlation Studies in Apple Cultivars of South Kashmir - Amit Kumar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
A study was conducted to assess agronomic performance and heritability estimates among different cultivars of apple in district Pulwama of Kashmir valley. Twenty cultivars aged 20 to 22 years were selected for the present study. Data were collected on physical and chemical characters of fruit and yield of the tree. Results revealed that 'Red Delicious' (315.43kg) and Ambri (310.40kg) Difenoconazoled highest yield among all the cultivars. Red Delicious apple recorded maximum fruit weight (182.63g). maximum TSS (16.35%) and total sugars (12.11%) with least acidity (0.07%) was recorded in Ambri apples. All the characters studied showed high heritability estimates except for cropping efficiency (61.06%) which scored least heritability. Length (0.843) and breadth (0.854) of fruit positively and significantly correlated with weight of the fruit. Acidity was negatively correlated with all other biochemical characters.